ISLAMIC TRADITIONS IN BIMA ETHNIC CULTURES: FROM LIVING TRADITION TO LEAVING TRADITION (International Conference on Social and Islamic Studies, 2021)
Bima ethnics were the genealogies of specific ethnic who once strongly upheld the traditions and local cultures in their everyday life. The local understanding of the Bima ethnics was reflected in the idea of their local wisdom and cultural spirit embedded in the fundamental values of Islamic teaching and tradition that considered as moral attitudes and guidance to control their behavior and morality in their daily basis either in private sphere or in social sphere. There are at least two cultural values that were strongly influenced by Islamic teachings and traditions, namely Maja Labo Dahu (Shamed and Scared) and Nggahi Rawi Pahu (Speech according to actions). Those cultural values can be considered as living traditions because those local wisdoms reflected in people everyday life in the past. Besides, those terms have been a slogan for Bima and Dompu regency as a way of Bima ethnic moral life that shaped how they conduct elite life in government and human’s everyday life in society. On the other hand, those cultural values are not strongly reflected in Bima youth generation nowadays. This case is what I call as leaving tradition because the cultures of Maja Labo Dahu and Nggahi Rawi Pahu have gradually disappeared in Bima society nowadays. Therefore, the main question of this article is (1) How does the construction of Islamic teaching and tradition uphold in Bima cultural life? and (2). Why does the value of Bima cultures not gradually apply in their daily basis nowadays? This research employs qualitative research, with data analyses of literature review from academic article, journal, and thesis.